2019
DOI: 10.1249/mss.0000000000002170
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Coordination in Chronic Ankle Instability, Coper, and Control Groups in Running

Abstract: Purpose Coordination and coordination variability have been used as a measure of the function and flexibility of the sensorimotor system during running. Chronic ankle instability (CAI) is associated with altered sensorimotor system function compared with individuals without CAI. Copers may have adopted protective sensorimotor adaptations to prevent repeated ankle sprains; however, their coordination strategies between the foot and shank have not been investigated. We compared joint coupling angles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Those that go on to develop CAI may be differentiated from copers based on their movement patterns, including dynamic balance, 105,116,205,250,352 walking, 50,106,136,456 stepping down, 49,125 running, 259 and landing from a jump, 111 with copers having biomechanics more similar to those of healthy individuals. 49,50,105,116,125,136,205,259,352 The neuromuscular ankle strategies adopted by copers may allow them to prevent recurrent symptoms.…”
Section: IIImentioning
confidence: 99%
“…Those that go on to develop CAI may be differentiated from copers based on their movement patterns, including dynamic balance, 105,116,205,250,352 walking, 50,106,136,456 stepping down, 49,125 running, 259 and landing from a jump, 111 with copers having biomechanics more similar to those of healthy individuals. 49,50,105,116,125,136,205,259,352 The neuromuscular ankle strategies adopted by copers may allow them to prevent recurrent symptoms.…”
Section: IIImentioning
confidence: 99%
“…There were no significant differences in height, mass, or age among the groups, as summarized in Table 2 . 26 The CAIT and FAAM-ADL scores in the CAI group were significantly lower than those in the coper and control groups ( P < .05 for both).…”
Section: Resultsmentioning
confidence: 77%
“…There are a limited number of studies investigating the variability of lower extremity motion of copers compared with CAI and control groups. 10 , 18 , 19 , 26 However, the previous studies have demonstrated conflicting results. For example, Herb et al 18 found that copers demonstrated less variability of ankle frontal motion than individuals with CAI during a jumping task, and control participants demonstrated greater knee and hip variability than copers and individuals with CAI during a jump landing task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated changes in the movement patterns of hips, knees, and ankles in individuals with chronic ankle instability (2,6,22) , demonstrating that the same condition can lead to different motor adaptations and each case requires individual evaluation. The motor variability among these individuals may reflect either an attempt to explore alternative stabilizing strategies or an inadequate sensory-motor control (23) .…”
Section: Functional Stability Mechanisms Of the Anklementioning
confidence: 99%